2009
DOI: 10.1002/pip.934
|View full text |Cite
|
Sign up to set email alerts
|

Shunt removal and patching for crystalline silicon solar cells using infrared imaging and laser cutting

Abstract: Shunts in crystalline silicon solar cells can be physically removed and replaced with good cells to eliminate their influences, which is proved by the experiments in this paper. By infrared imaging and laser cutting, the shunted regions near the edges of cell A and in the middle of cell B were identified and removed with their efficiencies increased by 6Á8% and 3Á0%, respectively. After shunt removal, cell B was patched up with good cells and its final work current further increased from 3Á71 to 4Á11 A. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In such a situation, it has been found that [10,11], a significant reverse current can flow through the shaded cell and this can lead to a premature break down and permanent degradation, because the current is observed to flow through the shunt resistance. It would be interesting to understand the possible improvement in the photovoltaic module performance, with either removal of shunts [12,13] or their isolation [14,3,15] or preventing them from occurring at least in the most detrimental locations during cell production. The aim of the present work is to present a systematic study of influence of ohmic shunts at significant spatial locations in an industrial Silicon photovoltaic module.…”
Section: Introductionmentioning
confidence: 99%
“…In such a situation, it has been found that [10,11], a significant reverse current can flow through the shaded cell and this can lead to a premature break down and permanent degradation, because the current is observed to flow through the shunt resistance. It would be interesting to understand the possible improvement in the photovoltaic module performance, with either removal of shunts [12,13] or their isolation [14,3,15] or preventing them from occurring at least in the most detrimental locations during cell production. The aim of the present work is to present a systematic study of influence of ohmic shunts at significant spatial locations in an industrial Silicon photovoltaic module.…”
Section: Introductionmentioning
confidence: 99%
“…It will be very useful and relevant to industry in classifying the shunts in different categories based on the level of severity in order to tackle the shunting problem during production. Shunts which cause more reduction in output power may be removed or isolated using laser technique [5,6] and leaving out those shunts which cause relatively low loss in efficiency of the cell. Also, corrective steps in production can be taken up based on severity of shunts in order to remove the origin of these process induced shunts.…”
Section: Introductionmentioning
confidence: 99%
“…Current applications for infrared imaging and thermography include: detection, diagnosis and prognosis of breast cancer [25,26], study of skin toxicities and tumor control in BNCT melanoma treatments [27], plant species identification [28], solar physics [29], astronomy [30], civil engineering [31], atmospheric wind velocity detection [32], maritime surveillance systems [33], imaging missile seekers [34], gas detection [35,36], and nondestructive detection in multiple fields of technology [37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%